Quarter Life Crisis Dengan Turnover Intention Pada Generasi Z - Arifiani, Zefi Nafira; Ardy Wiratama (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Turnover intention is an individual's activity of leaving work of his own accord Quarter-life crisis individuals experience fear of facing life in the future. This study uses a quantitative correlational approach. While the independent variable in this study is quarter of life and the dependent variable is turnover instruction. The population in the study was gen z with 50 respondents. The sample was taken by purposive sampling. Data analysis tests used normality and hypothesis tests. The results of this study state that there is a relationship between quarter life crisis and turnover intention in the gen z generation.